2020
DOI: 10.1590/1981-22562020023.200171
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of and mortality from COVID-19 in the older Brazilian population and its relationship with contextual indicators: an ecological study

Abstract: Objective: to analyze the incidence of and mortality caused by COVID-19 in the older population in Brazil and its relationship with contextual variables. Methods: the 22 Brazilian states (including the Federal District) with 50 deaths or more due to COVID-19 by May 25th, 2020 were included. The rates of accumulated incidence, accumulated mortality and accumulated lethality among older adults were considered as dependent variables. Among the contextual variables, the provision of health services and profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
23

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 20 publications
1
23
0
23
Order By: Relevance
“…The influence of contextual sociodemographic factors related to skin color and income on mortality rates due to COVID-19 in older adults was also verified. 8 The presence of comorbidities proved to be the factor with the greatest effect for the occurrence of deaths from COVID-19. The presence of comorbidities increases the risk of death by 9.44 times compared to individuals with no comorbidities.…”
Section: Discussionmentioning
confidence: 95%
“…The influence of contextual sociodemographic factors related to skin color and income on mortality rates due to COVID-19 in older adults was also verified. 8 The presence of comorbidities proved to be the factor with the greatest effect for the occurrence of deaths from COVID-19. The presence of comorbidities increases the risk of death by 9.44 times compared to individuals with no comorbidities.…”
Section: Discussionmentioning
confidence: 95%
“…Baqui et al [ 29 ] found higher mortality in the brown and black populations, highlighting brown ethnicity as the second leading risk factor for death, next to age. Barbosa et al [ 30 ] observed that incidence rate and mortality rate also revealed, respectively, a significant positive correlation with the proportion of black (Afro-Brazilian) and brown (mixed race) skinned people and with the income ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Mesmo com o fato dos idosos serem menos acometidos pela doença no estado, é visto no estudo de Barbosa et al, (2020) Research, Society andDevelopment, v. 9, n. 11, e3539119884, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i11.9884 escala deste fenômeno, incidem outras variantes, como a presença majoritária delas no "front" profissional da saúde ou em atividades de alta exposição, como limpeza (Soares, 2020).…”
Section: Resultsunclassified